Safety, pharmacokinetics, and pharmacodynamic activity of obinutuzumab, a type 2 anti‐CD20 monoclonal antibody for the desensitization of candidates for renal transplant. Issue 11 (23rd July 2019) - Redfield, Robert R.; Jordan, Stanley C.; Busque, Stephan; Vincenti, Flavio; Woodle, E. Steve; Desai, Niraj; Reed, Elaine F.; Tremblay, Simon; Zachary, Andrea A.; Vo, Ashley A.; Formica, Richard; Schindler, Thomas; et al.
Abstract : The limited effectiveness of rituximab plus intravenous immunoglobulin (IVIG) in desensitization may be due to incomplete B cell depletion. Obinutuzumab is a type 2 anti‐CD20 antibody that induces increased B cell depletion relative to rituximab and may therefore be more effective for desensitization. This open‐label phase 1b study assessed the safety, pharmacokinetics, and pharmacodynamics of obinutuzumab in highly sensitized patients with end‐stage renal disease. Patients received 1 (day 1, n = 5) or 2 (days 1 and 15; n = 20) infusions of 1000‐mg obinutuzumab followed by 2 doses of IVIG on days 22 and 43. Eleven patients received additional obinutuzumab doses at the time of transplant and/or at week 24. The median follow‐up duration was 9.4 months. Obinutuzumab was well tolerated, and most adverse events were grade 1‐2 in severity. There were 11 serious adverse events (SAEs) in 9 patients (36%); 10 of these SAEs were infections and 4 occurred after kidney transplant. Obinutuzumab plus IVIG resulted in profound peripheral B cell depletion and appeared to reduce B cells in retroperitoneal lymph nodes. Reductions in anti‐HLA antibodies, number of unacceptable antigens, and the calculated panel reactive antibody score as centrally assessed using single‐antigen bead assay were limited and not clinically meaningful for most patients (NCT02586051). Abstract : The authors assess the safety, pharmacokinetics, and pharmacodynamics of obinutuzumab in combination with high‐dose intravenous immunoglobulins in highly sensitized patients with end‐stage renal disease awaiting kidney transplantation and find that obinutuzumab is tolerated well and effectively depletes B cells, but has limited effects on reducing pre‐existing anti‐HLA alloantibody levels.